2004
DOI: 10.1590/s1519-38292004000300006
|View full text |Cite
|
Sign up to set email alerts
|

O aleitamento materno previne o sobrepeso na infância?

Abstract: Objectives: to investigate if breast feeding has a protective effect against overweight in preschool age.Methods: cross-sectional study with 409 children, two to six years old, 221 boys and 188 girls, in Recife. The exposition was exclusive breast feeding for less than four months. The outcome was overweight, defined as body mass index (BMI) by age equal or above the 85 th percentile.Results: among the 409 children, 11.5% were never breastfed. Mean breast feeding duration was 3.97 months. Overweight prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
19

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
(25 reference statements)
0
5
0
19
Order By: Relevance
“…While some researchers consider as inconclusive the evidence that breastfeeding is a protective factor against childhood obesity,26 in the last decade others have concluded that exclusive breastfeeding protects against excess weight in preschool and school-age children 521 Hediger et al,27 in the United States, concluded that the preschoolers that had been breastfed had a lower risk of being obese, but not of being overweight.…”
Section: Discussionmentioning
confidence: 99%
“…While some researchers consider as inconclusive the evidence that breastfeeding is a protective factor against childhood obesity,26 in the last decade others have concluded that exclusive breastfeeding protects against excess weight in preschool and school-age children 521 Hediger et al,27 in the United States, concluded that the preschoolers that had been breastfed had a lower risk of being obese, but not of being overweight.…”
Section: Discussionmentioning
confidence: 99%
“…The variables related children were: age in months, categorized into two age groups (24 to 36 incomplete months and 36 months to 60 months); 15 gender; ethnicity referred by the mother (white and non-white); type of delivery (vaginal and cesarean section); birth weight (< 4,000g and ≥ 4,000 g); 18 received breastfeeding (yes or no); time to exclusive breastfeeding (< 4 months and ≥ 4 months). 19 In relation to the variables related to day-care centers, were studied (if the children enrolled in a public or affiliated day care); age from children who attended day care center (≤ 12 months and > 12 months) and the adequacy of food intake, energy, lipid, carbohydrate and protein offered in day care (≤100% and >100% recommendation). The variable categorized was performed using previous references for comparison and distribution from the mean and quartiles.…”
Section: Methodsmentioning
confidence: 99%
“…Balaban et al, 37 observaram que a prevalência de sobrepeso foi maior em pré-escolares que mamaram exclusivamente por menos de quatro meses comparadas aos que mamaram por quatro meses ou mais. Kalies et al, 38 verificaram que o prolongamento do tempo de aleitamento materno exclusivo reduz o risco para o elevado ganho de peso até os dois anos e que esta associação foi altamente dose-dependente.…”
Section: Gonçalves Fclsp Et Alunclassified